PENERAPAN USER CENTERED DESIGN PADA PERANCANGAN WEB E-COMMERCE ALAT KESEHATAN - Isnaini Hayati; Ayuningtyas Ayuningtyas; Erwin Sutomo (Jurnal Informatika Universitas Pamulang, 2022)
CV. Andi Jaya is a form of business entity that was established on August 31, 2010, in the city of Surabaya, precisely at Jalan Merak Raya Rewwin No.6. CV Andi Jaya is a company that provides cheap medical devices in Surabaya. Based on the results of direct interviews with customers who have purchased goods through the website, there are several obstacles felt by customers, namely the process of selling goods on the website does not go well, there are several menus that cannot be accessed by users, the appearance of the website makes users not interested in making purchases such as product catalog is not well organized. Apart from the customer side, there are several obstacles in the business process, namely in the process of recording transactions the data is not updated in real time so that incomplete records often occur and the admin and users cannot see the status of ordering goods. From the prototype, an evaluation was carried out by distributing a system usability scale (SUS) questionnaire to 26 respondents to evaluate the product and as a benchmark for user perceptions. From the results of testing the prototype, an average of 73.6 is included in the "good" category, which means that the design is accepted by the user.